Sentimentos de mães de crianças com paralisia cerebral: estudo iluminado na teoria da incerteza na doença - Gondim, Kamilla de Mendonça (2009)
Cerebral palsy is a cronic, irreversible, non-progressive patology that occurs during the fetal development of the brain, provoking motor-sensorial changes which limit the development of a child when accomplishing daily tasks. These changes affect not only the child’s life quality, but also the whole family envolved. The moment a child is diagnosed as having brain paralysis is a painful one and is always surrounded by fear and uncertainties. Considering this context, greater attention should be devoted to the mother since, she’s the one who is responsible for childcare and household tasks. Therefore, this study has as a main goal, to analyse, from the mother’s perception, the uncertainty in her brain paralysis affected child, based on Uncertainty During Desease Theory, of Mishel. Such theory deals with the uncertainties, anxiety and questionings, provoking stress in those envolved, since they don’t know about their child’s future. It is a descriptive study, based on a qualitative, investigative perspective, accomplished at the Núcleo de Tratamento e Estimulação Precoce – NUTEP and at the children’s hospital Albert Sabin between July and August 2009.Twelve mothers took part in the study about brain paralysis affected children who were under care in the services mentioned above. The gathering of data was made through forms filled with social and demographics information about the mothers and also through a semi-structured interview composed by data related to Mishel’s Theory according to a parents/children version. Data was analysed based on the Content Analysis proposed by Bardin. Among the studies, twelve thematic categories have been highlighted as follows: The awereness of the mother about her child’s diagnosis as well as its severity, the moment of the diagnosis and its future implications, future plans, help during childcare, improvemnt of explanation about the illness, knowledge about the professional’s proposes, presence of questionings, previews and changes in the chid’s health situation. During the research we have noticed that the mothers lack information and show feelings of uncertainty about their children’s patology, mainly about the future. Such uncertainties may be reduced by the professionals of health, promoting a better relationship with the mothers, clarifying their questions, as well as aquiring information about the patology and all the process of treatment and even giving opportunities for a feedback about the child’s evolution. These aspects will work as a tool to reduce their questions and, consequently their uncertainties. The study is a contribution of knowing in the scene of the neurological nursing, since anchored in the questions of the promotion of the health aiming the improvement of the quality of life of these children and his family.